Coprecipitation technique to prepare ZnM2O6 powders - Deshpande, V. V.; Patil, M. M.; Navale, S. C.; Ravi, V. (Bulletin of Materials Science, 2005)
A simple coprecipitation technique was successfully applied for the preparation of pure ultrafine single phase, ZnNb2O6 (ZN). Ammonium hydroxide was used to precipitate Zn2+ and Nb5+ cations as hydroxides simultaneously. This precursor on heating at 750 degrees, produced ZN powders. For comparison, ZN powders were also prepared by the traditional solid state method. The phase contents and lattice parameters were studied by the powder X-ray diffraction (XRD). Particle size and morphology were studied by transmission electron spectroscopy (TEM).
Keywords: Ceramics; Electron microscopy; electronic materials; X-ray diffraction